2021
DOI: 10.1007/s12026-021-09178-4
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune liver disease-associated serologic profiling in Chinese patients with acute hepatitis E virus infection

Abstract: The association between hepatitis E virus (HEV) and autoimmune liver diseases has been well-researched; however, the focus has been on autoimmune hepatitis (AIH) and not primary biliary cholangitis (PBC). Therefore, we aimed to investigate the prevalence and evolution of AIH- and PBC-related autoantibodies in Chinese patients with HEV infection. In this retrospective study, 164 patients with acute HEV were included, specifically those whose liver autoantibody results were available and who had no pre-existing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…HEV is classically associated with circulating liver-directed autoantibodies. Reports by Gui et al found that following acute HEV, 7.7% of patients may have circulating anti-mitochondrial antibody (AMA) or ANA [ 9 ]. Another study by Piccoli et al [ 9 ] found that acute HEV infection may present with circulating autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HEV is classically associated with circulating liver-directed autoantibodies. Reports by Gui et al found that following acute HEV, 7.7% of patients may have circulating anti-mitochondrial antibody (AMA) or ANA [ 9 ]. Another study by Piccoli et al [ 9 ] found that acute HEV infection may present with circulating autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Reports by Gui et al found that following acute HEV, 7.7% of patients may have circulating anti-mitochondrial antibody (AMA) or ANA [ 9 ]. Another study by Piccoli et al [ 9 ] found that acute HEV infection may present with circulating autoantibodies. Among 48 patients with acute viral hepatitis half of them had circulating liver-directed autoantibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the virus may worsen preexisting liver abnormalities, which can lead to a more rapid development of liver disease as well as an increased risk of liver failure. The acute liver failure that may result from an HEV infection in certain people is a condition that poses a significant risk to their lives [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we found that AMA was also detectable in patients with other autoimmune diseases, which was consistent with previous reports. [ 21 , 22 , 23 , 24 , 25 ] Of note, like in many medical centers in China, in our institute AMA is included in the panel of ANA testing and routinely ordered for patients with suspected rheumatologic disorders, or patients with fever of unknown origin from various departments, especially from rheumatology department. This may partially explain the relatively high proportion of patients with autoimmune diseases in AMA‐positive patients in the current study.…”
Section: Discussionmentioning
confidence: 99%